Rehabilitation for Patients with COVID-19-Associated Acute Respiratory Distress Syndrome During Quarantine: A Single-Center Experience - Myung Hun Jang; Yong Beom Shin; Ho Jeong Shin; Eunsuk Jeong; Saerom Kim; Wanho Yoo; Hyojin Jang; Kwangha Lee (Medicina)
Background and Objectives: In this study, we evaluated clinical factors associated with implementing a rehabilitation program for patients with COVID-19-associated acute respiratory distress syndrome (ARDS) requiring mechanical ventilation (MV) during the quarantine period. Materials and Methods: This observational study was conducted in the National Designated Isolated ICU, a dedicated COVID-19 center with 18 beds, from 30 December 2020 to 30 May 2022. One hundred and fifty-four patients (mean age: 67.3 ± 13.4 years; male: 59.7%) were enrolled. The ICU rehabilitation program included early mobilization, chest physiotherapy, and dysphagia treatment. Results: Forty-five patients (29.3%) participated in the rehabilitation program. Multivariate logistic regression identified three significant factors: tracheostomy (odds ratio [OR], 2.796; 95% confidence interval [CI], 1.238–6.316; p = 0.013), body mass index ≥ 25.0 kg/m2 (OR, 2.724; 95% CI, 1.276–5.817; p = 0.010), and extracorporeal membrane oxygenation (OR, 2.931; 95% CI, 1.165–7.377; p = 0.022); patients with all three factors were younger (median 44 vs. 70 years, p < 0.001) and had significantly lower Acute Physiology and Chronic Health Evaluation II scores (median 12 vs. 16, p = 0.002) on the MV day. One-year cumulative mortality rates for patients with 0 to 3 factors were 66.7%, 50.8%, 38.9%, and 15.4%, respectively, with a significant difference among them (log-rank, p < 0.001). Conclusions: Three clinical factors associated with implementing a rehabilitation program during the quarantine period for COVID-19-associated ARDS patients were identified. The program was feasible and beneficial, particularly for younger patients with lower illness severity and fewer comorbidities on the day of MV.